Cultural-Based Analysis of Local Language Diversity in Quantity and Measurement Concepts: An Ethno-Creative Physics Study - John Batlolona Batlolona; Jamaludin Jamaludin; Yohanis Hukubun; Mehmet Altan Kurnaz (Yayasan Keluarga Guru Mandiri, 2026)
This research focuses on the concepts of physics, namely quantities and units found in local wisdom in Maluku. However, to our knowledge, there are only a few empirical studies examining how the concepts of quantities and units in creativity studies, especially in the island communities of Maluku. Previous studies have primarily focused on what has been established by international committees with standardized measurement. Meanwhile, traditional measurement systems are still applied in daily activities. The socio-cultural diversity in this miniature region is beneficial for connecting local wisdom with physics learning. Therefore, the aim of this study is to analyze students' creativity in the concepts of quantities and units based on Maluku's local wisdom. This research was conducted through observation, interviews, and documentation, revealing a relationship between various aspects of local wisdom in Maluku and physics concepts. Several examples of local wisdom identified include local language in the trading system or other activities in the region. The study results show that students can describe local wisdom in physics related to the concepts of quantities and units based on four indicators of creative thinking. This local wisdom can serve as an object in physics learning that is highly relevant to the Merdeka Curriculum, facilitating students' understanding of the material being taught.